Case report: Electroacupuncture for acute pain flare-up of knee osteoarthritis - Huang, Hai; Liang, Yongying; Han, Dapeng; Chen, Xiaoyan; Xiao, Lianbo; Wu, Hongyan (Frontiers in Neurology, 2022)
Acute pain flare-up of knee osteoarthritis (KOA) is a common disease in orthopedics, for which analgesic drugs remain the main treatment. Patients refuse to take western medicine orally because of their gastrointestinal side effects or unsatisfactory effect. In our case study, a 69-year-old woman had an acute pain flare-up of right KOA induced by long-distance walking. As the patient refused medication, we used electro-acupuncture (EA) to relieve her symptoms. EA with a 2-Hz frequency and a 1–2-mA intensity had an analgesic effect on the acute pain flare-up of KOA. After 12 weeks of EA intervention, the bone marrow edema-like lesions (BMLs) shown in the magnetic resonance imaging of the knee joint of the patient had obviously improved. However, more powerful evidence is needed to understand mechanism of the EA technique that alleviates BMLs of KOA.